Sexual harassment of the physiotherapist in South Africa - L. Bütow-Dûtoit; C. A. Eksteen; M. De Waal; J. H. Owen (AOSIS, 2006)
No study  has been conducted on sexual harassment of physiotherapists in South Africa and it is therefore not known whether harassment occurs and if it does, to what extent. To this purpose, a questionnaire on  sexual harassment and other sexual-related issues in the physiotherapy work environment in South Africa, was sent to a random selection of  982 physiotherapists registered with the Health Professions Council of South Africa. The response rate was 32%. This paper presents the results of the first half of the questionnaire, which was devoted to sexual harassment of the physiotherapist.  Approximately 60% had experienced sexual harassment, of which 83.98% had been perpetrated by patients. Only 5.82% of the respondents had received some form of information in this regard. The most common form of harassment was requests for a hug or kiss.